Bond strength and micro-computed tomographic evaluation of pre-coated brackets - Bakhadher Waleed; Talic Nabeel; Al Hezaimi Khalid (Sciendo, 2015)
The aim of the present study was to assess and compare the shear bond strength (SBS) of metal pre-coated orthodontic brackets bonded to fluorotic and non-fluorotic teeth treated with three different etching techniques. A second aim was to determine the volume of adhesive remaining on the tooth at debond using micro-computed tomography (μCT).